Zarządzanie SOP na przykładzie firmy Danone Polska - Wolczek, Przemysław (Corporate Social Responsibility Management in Danone, 2009)
In this article the approach of Danone Poland to the matter of corporate social responsibility is presented. The activities of the company with reference to employees, consumers, suppliers, society as well as natural environment are described. The managing of social responsibility presented by Danone Poland can be a good example for the companies which want to conduct their business in agreement with the principles of sustainable development.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 187-196